CRYSTAL STRUCTURE OF [Bis(DIMETHYLFORMAMIDE) Bis(2,2’-PYRIDYL)QUINOLINE)IRON(II)]Bis-(TETRAPHENYLBORATE) (Makara Journal of Science, 2009)
The goal of this research is to obtain single crystal and structural information of iron(II) complex with 2,(2’- pyridyl)quinoline(pq) ligands. The reaction of iron(II) salt with 2,(2’-pyridyl)quinoline ligand and sodium tetraphenylborate in the molar ratio of 1:3:2 in methanol-N,N-dimethylformamide(dmf) solution results in an iron(II) complex. The formula of the [Fe(pq)2(dmf)2](BPh4)2 complex has been obtained from the iron(II) and C, H, N contents. Single crystal of [Fe(pq)2(dmf)2](BPh4)2 suitable for X-ray investigation was obtained by evaporation of the complex solution in N,N-dimethylformamide at room temperature after 24 hours. This compound crystallizes in monoclinic system with C2/c space group, a = 27.950(4), b = 14.169(7), c = 17.717(9) Å and β = 105.669(11)°. The structure consist of iron(II) is chelated by two pq ligands through the N atoms and two dmf molecules in a six-coordination environment. The charge of the [Fe(pq)2(dmf)2] 2+ cation is balanced by two tetraphenylborate (BPh4) - anions.